AN ANALYSIS OF FLOUTING MAXIMS IN CONVERSATION SPEAKING OF THE MAIN CHARACTER IN THE MOVIE OF HOME ALONE 2 “LOST IN NEW YORK” BY JOHN HUGHES - Nursuci Gunawan Lestari; Jauhar Helmie (Universitas Suryakancana, 2019)
Communication is a human activity everyday, people always communicate each other. Sometime people do not realize what they are talking about. To make a good communication, human must follow cooperative principles. That is why Grice offers to use theory of cooperative principle to avoid misunderstanding and misinterpretation between the speaker and the listener. However, some people do not fulfill those maxims to be used in the conversation for certain reasons, and when they violate the maxims it is called flouting maxims. A descriptive qualitative approach is used for this study because the data are in the form of words rather than of numbers and statistics. This study reveals that based on theory of Grice’s Cooperative, there are four maxims which are flouted by the main characters of “Home Alone Part 2 ‘Lost in New York’” movie this movie since 1992 directed and written by John Hughes. The result shows that there are four Maxims Flouted by the main characters there are flouting maxim of quality, flouting maxim of quantity, flouting maxim of relevance, and flouting maxim of manner. And there are several reasons of flouting those maxims are data finding also revealed that the communication could still even though the main characters flouting the maxims. Four reasons by the main characters to flout the maxims are competitive, collaborative, convivial, and conflictive reason. In terms of types, quantity maxim flouting is in the highest rank and relevance maxim flouting is in the lowest rank. In terms of strategies, overstatement is the most frequently used and metaphor is the most rarely used. Finally, dealing with reasons for maxim flouting, conflictive reason has the highest rank in its occurrence.Communication is a human activity everyday, people always communicate each other. Sometime people do not realize what they are talking about. To make a good communication, human must follow cooperative principles. That is why Grice offers to use theory of cooperative principle to avoid misunderstanding and misinterpretation between the speaker and the listener. However, some people do not fulfill those maxims to be used in the conversation for certain reasons, and when they violate the maxims it is called flouting maxims. A descriptive qualitative approach is used for this study because the data are in the form of words rather than of numbers and statistics. This study reveals that based on theory of Grice’s Cooperative, there are four maxims which are flouted by the main characters of “Home Alone Part 2 ‘Lost in New York’” movie this movie since 1992 directed and written by John Hughes. The result shows that there are four Maxims Flouted by the main characters there are flouting maxim of quality, flouting maxim of quantity, flouting maxim of relevance, and flouting maxim of manner. And there are several reasons of flouting those maxims are data finding also revealed that the communication could still even though the main characters flouting the maxims. Four reasons by the main characters to flout the maxims are competitive, collaborative, convivial, and conflictive reason. In terms of types, quantity maxim flouting is in the highest rank and relevance maxim flouting is in the lowest rank. In terms of strategies, overstatement is the most frequently used and metaphor is the most rarely used. Finally, dealing with reasons for maxim flouting, conflictive reason has the highest rank in its occurrence.